PENGEMBANGAN EKOSISTEM KEWIRAUSAHAAN DESA BERBASIS SEKOLAH PEREMPUAN DAN TEKNOLOGI PRODUKSI PASCA PANEN DESA PURWOBINANGUN PAKEM SLEMAN YOGYAKARTA - Arif Fajar Wibisono; Satyaguna Rahmatulloh; Latifatul Laili (Jurnal Abdi Insani, 2026)
The development of Purwobinangun Village’s potential, particularly in post-harvest management, continues to face significant challenges. This article discusses a community engagement program implemented in Purwobinangun Village, Sleman, Yogyakarta, aimed at addressing challenges in post-harvest management and livestock business development. The program was designed to overcome the absence of local institutions—particularly those involving rural women—that can effectively manage and innovate post-harvest production. Through non-formal institutionalization, the program empowered women farmers to plan, implement, and evaluate entrepreneurial activities in a structured and sustainable manner. As a result, participants successfully developed a range of value-added dairy products, including pasteurized milk, milk sticks, milk candy, milk sponge cake, and milk pudding. The program also facilitated the preparation of a production and business curriculum, assisted in obtaining PIRT and halal certification, and significantly improved participants’ competencies in business planning, marketing strategy, and financial accountability. The long-term goal is to create resilient, economically independent women who can sustain post-harvest processing activities and livestock-related businesses, thereby contributing to improved family welfare and advancing the vision of Purwobinangun as a self-reliant, economically empowered entrepreneurial village.